Simplistic correlations between molecular electronic properties and inhibition efficiencies: Do they really exist?. (February 2021) - Kokalj, Anton; Lozinšek, Matic; Kapun, Barbara; Taheri, Peyman; Neupane, Shova; Losada-Pérez, Patricia; Xie, Chenyang; Stavber, Stojan; Crespo, Daniel; Renner, Frank U.; Mol, Arjan; Milošev, Ingrid
Graphical abstract: Highlights: Simplistic correlations between molecular parameters and corrosion inhibition efficiencies critically evaluated. 24 heterocyclic organic compounds tested as corrosion inhibitors for Cu in 3 wt.% NaCl aqueous solution. None among usually considered molecular parameters correlates with inhibition efficiency. Pros and cons of the inhibition efficiency (IE) metric discussed: IE suffers from nonlinearity. Inhibition power proposed as a new metric for evaluating the performance of corrosion inhibitors. Abstract: The often used simplistic correlations between molecular electronic parameters and experimentally determined corrosion inhibition efficiencies are critically evaluated for a set of 24 heterocyclic organic compounds, tested as corrosion inhibitors for copper in 3 wt.% NaCl aqueous solution. Twelve different molecular electronic descriptors—such as ionization potential, electron affinity, HOMO–LUMO gap, dipole moment—are tested and it is shown that none of them displays any noticeable correlation with the inhibition efficiency. Our results, therefore, cast serious doubt on reported correlations between such parameters and inhibition efficiency, obtained for only a few inhibitors, which are abundant in the literature. We also discuss some pros and cons of inhibition efficiency as a metric for evaluating the performance of corrosion inhibitors, and introduce a new metric termed inhibition power that uses the universal logarithmic scale and dimensionless decibel (dB) units.